2020
DOI: 10.1111/tmi.13385
|View full text |Cite
|
Sign up to set email alerts
|

Household flooring associated with reduced infant diarrhoeal illness in Zimbabwe in households with and without WASH interventions

Abstract: Objectives: Diarrheal illness is a leading cause of childhood morbidity and mortality and has longterm negative impacts on child development. Although flooring, water, and sanitation have been identified as important routes of transmission of diarrheal pathogens, research examining variability in the association between flooring and diarrheal illness by water and sanitation is limited.Methods: We utilized cross-sectional data collected for the evaluation of Zimbabwe's Prevention of Mother-to-Child HIV transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…A study from Zimbabwe showed that mothers of infants living in households with improved ooring were less likely to report diarrheal illness. Further, the association between ooring and diarrheal illness did not vary by the presence of improved/unimproved water or sanitation [23]. It was also found that dirt and mud oors are a known predictor of diarrhea and parasitic infestations [23,24].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A study from Zimbabwe showed that mothers of infants living in households with improved ooring were less likely to report diarrheal illness. Further, the association between ooring and diarrheal illness did not vary by the presence of improved/unimproved water or sanitation [23]. It was also found that dirt and mud oors are a known predictor of diarrhea and parasitic infestations [23,24].…”
Section: Introductionmentioning
confidence: 82%
“…Further, the association between ooring and diarrheal illness did not vary by the presence of improved/unimproved water or sanitation [23]. It was also found that dirt and mud oors are a known predictor of diarrhea and parasitic infestations [23,24]. Eliminating a dirt oor from the home results in dramatic reductions in childhood diarrhea and Soil-Transmitted Helminth (STH) [23,25].…”
Section: Introductionmentioning
confidence: 97%
“…34 A cross-sectional study in Zimbabwe reported a statistically significant 18% percent lower diarrhea prevalence in infants living in homes with finished floors. 32…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies in urban and rural settings have reported associations between living in a household with a soil floor and higher risk of infection with hookworm 23 , A. lumbricoides 22,24,25 , Strongyloides stercoralis 26 , G. duodenalis 24,27 , cholera, 28 other enteric parasite infections, 29–31 and diarrhea or gastrointestinal illness. 32,33 A retrospective, matched impact evaluation of a government program in urban Mexico found that replacing household dirt floors with concrete reduced diarrhea and intestinal parasite infection in children. 34 However, this study did not describe the parasite species that were measured.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in 'healthy homes' and infectious disease, which at this stage has been primarily focused on vector control; however, there is an urgent need to assess the relationship between the built environment and its impact on enteric infection risk. While some observational studies have suggested no association between unimproved flooring and enteric pathogen risk, multiple observational studies have shown associations between unimproved flooring and diarrhoeal risk [16] as well as some enteric parasitic infections, notably STH [9]. However, no systematic review of the literature has been conducted, to our knowledge, to assess whether unimproved household flooring is an independent risk factor for enteric disease risk in low-and middle-income countries (LMIC).…”
Section: Introductionmentioning
confidence: 99%